Social context affects tail displays by Phrynocephalus vlangalii lizards from China - Peters, Richard A. (Sci Rep, 2016)
Competition between animals for limited resources often involves signaling to establish ownership or dominance. In some species, the defended resource relates to suitable thermal conditions and refuge from predators. This is particularly true of burrow-dwelling lizards such as the Qinghai toad-headed agama (Phrynocephalus vlangalii), which are found on the Tibetan plateau of western China. Male and female lizards occupy separate burrows, which are vital for anti-predator behaviour during warmer months when lizards are active and, crucially, provide shelter from harsh winter conditions. These lizards are readily observed signaling by means of tail displays on the sand dunes they inhabit. Given the selective pressure to hold such a resource, both males and females should exhibit territorial behaviour and we considered this study system to examine in detail how social context influences motion based territorial signaling. We confirmed that territorial signaling was used by both sexes, and by adopting a novel strategy that permitted 3D reconstruction of tail displays, we identified significant variation due to social context. However, signal structure was not related to lizard morphology. Clearly, the burrow is a highly valued resource and we suggest that additional variation in signaling behaviour might be mediated by resource quality.